1961
DOI: 10.1039/jr9610001654
|View full text |Cite
|
Sign up to set email alerts
|

322. The biosynthesis of polyacetylenes. Part III. Polyacetylenes and triterpenes in Polyporus anthracophilus

Abstract: The maticaria ester (I) which occurs in P. unthmcophilus is derived from acetate by head-to-tail linkage. The polyacetylenes in this species are in a dynamic state, with synthesis de novo accompanying their disappearance. The incorporation of acetate into triterpenes proceeds simultaneously and may be very efficient; in different strains of the fungus competition between triterpene and polyacetylene synthesis is apparent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1963
1963
2008
2008

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Circa 1960, Polyporus anthracophilus feeding experiments with [1-14 C]acetate showed labeling of the odd-numbered carbons in matricaria ester 3D (Fig. 5) [55]. A related experiment demonstrated the alternating [1-14 C]acetate labeling of nemotinic and odyssic acids (3F, 3G) from basidiomycete B.…”
Section: 13mentioning
confidence: 95%
“…Circa 1960, Polyporus anthracophilus feeding experiments with [1-14 C]acetate showed labeling of the odd-numbered carbons in matricaria ester 3D (Fig. 5) [55]. A related experiment demonstrated the alternating [1-14 C]acetate labeling of nemotinic and odyssic acids (3F, 3G) from basidiomycete B.…”
Section: 13mentioning
confidence: 95%
“…Investigations with the higher fungus Polyporus anthracophilus (3) showed that its polyacetylenes were in a dynamic state, their synthesis de novo accompanying their disappearance. The dry rot fungus Merulius lacrymans (4) produced about 30 mg of poly-PREPARATIONS OF PASSICOL 109 acetylenes per liter of culture fluid when grown on corn steep liquor, and the concentration of polyacetylenes was maximal 50 days after inoculation.…”
Section: Resultsmentioning
confidence: 99%